Policy Implications of E-Government Development Index Trends: A Case Study of Middle Eastern Countries - Ramadhan, Sukma Aditya; Nurmandi, Achmad; Misran, Misran (Magister Ilmu Administrasi Publik, 2024)
This research aims to provide a thorough analysis of the progress of e-government in East Asia. By analyzing the annual survey of 192 UN member states, this article reviews 10 East Asian countries and their level of development in the E-Government Development Index (EGDI). The focus of the research is to analyze the development of e-government in the Middle East. Reviewing the E-Government Development Index (EGDI) of 10 Middle Eastern countries, the study highlights variability in e-government developments in the region. In particular, it noted Kazakhstan's progress due to infrastructure and education investments, as well as Afghanistan's challenges due to conflict and limited resources. These findings are important for understanding the context of E-Government in these countries and assisting policymakers in designing strategies to improve e-government services and development